2017
DOI: 10.1186/s12887-017-0838-4
|View full text |Cite
|
Sign up to set email alerts
|

Does sevoflurane add to outpatient procedural sedation in children? A randomised clinical trial

Abstract: BackgroundThere is little evidence concerning the effect of sevoflurane in outpatient procedural sedation, especially in children. We hypothesised that the addition of sevoflurane to a sedation regimen improves children’s behaviour with minimal adverse events.MethodsThis is a randomised, triple-blind clinical trial conducted on an outpatient basis. Participants were 27 healthy children aged 4 to 6 years, who previously refused dental treatment with non-pharmacologic methods. All participants received oral mida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In another study by Gomes et al [13], an oral midazolam + ketamine + nasal mask with oxygen group and nasal mask sedation concentration of sevoflurane + oxygen applied group were examined in children's oral dental treatment. In this pilot study, haemodynamic parameters (HR, oxygen saturation) were found to be similar during the procedure and at post -anaesthesia recovery.…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Gomes et al [13], an oral midazolam + ketamine + nasal mask with oxygen group and nasal mask sedation concentration of sevoflurane + oxygen applied group were examined in children's oral dental treatment. In this pilot study, haemodynamic parameters (HR, oxygen saturation) were found to be similar during the procedure and at post -anaesthesia recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events were “unexpected and undesirable responses to sedatives that threaten or cause patient injury or discomfort” [ 10 ] and were assessed according to the World SIVA International Sedation Task Force Tool [ 22 ] complemented by a previous publication when appropriate [ 23 ]. The same observer who accompanied the child throughout the dental sedation procedure registered any adverse event during the intra- or post-operative periods.…”
Section: Methodsmentioning
confidence: 99%
“…Midazolam is the drug most commonly used in this context, whereas other drugs such as ketamine have also demonstrated efficacy in behavioral control [ 7 , 8 ]. Moreover, it has been shown that administration of both ketamine and midazolam could be a good choice for pediatric dental sedation, including for very young children [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials also report the effects of some aids, such as art, music, or even the presence of domestic animals [11,14,15,16]. Furthermore, methods of conscious sedation and deep sedation are recognized, with the use of oral, intravenous, or gaseous drugs [17,18].…”
mentioning
confidence: 99%